Balanced Education According to Imam Al-Zarnuji - Khairul Nizam bin Zainal Badri (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
In traditional educational institutions, Ta‘līm al-Muta‘allim Tariq Al-Ta’allum by Imam Al-Zarnuji has a great influence in the field of teaching and learning, especially in the formation of the ethics of students when acquiring knowledge. This influence causes this book to be often studied in terms of the concept of science and pedagogy of education. But on the other hand, the importance of the balance of thought and behavior from a cognitive and moral point of view has not yet been studied in depth; whereas the goal of education according to Al-Zarnuji’s view is to produce human beings with personality and wisdom. Thus, education must lead to the development of human qualities in terms of intellectual, emotional, and spiritual balance. This study using a qualitative method with a content analysis approach seeks to explore the philosophy of integrated education contained in this book authored by Imam Al-Zarnuji. The results of the study found that monotheistic awareness is the main foundation in education because it not only stimulates the cognitive domain, but also the affective domain. With high awareness, man is not only able to perform his responsibilities to God which refers to vertical practices but is also able to perform his responsibilities to other human beings which refers to horizontal practices. Thus, it can be said that the philosophy of education emphasized by Al-Zarnuji in his writings is education based on a holistic view of knowledge.